Cubizpay: Information System In Credit Union - Yusuf, Rolland M; Paranoan, Selmita (International Journal of Accounting and Management Research, 2024)
The Credit Union has implemented information technology in the development of its services by presenting CubizPay. This study aims to determine the benefits of CubizPay in increasing member trust in Credit Union services. This research applies an interpretative approach with interpretative phenomenological analysis, to find out the meaning of user experience in accepting and using CubizPay through interviews and documentation with (5) Credit Union members who are active CubizPay users. This research found that the benefits of CubizPay can increase member trust through transaction transformation in member activities, which is equipped with a reliable security system to protect member transactions, as well as internal controls that help minimize risks in the Credit Union environment. CubizPay as an information system in Credit Unions is known to be able to increase member trust and help the Credit Union's operational activities. This research introduces CubizPay as an information system for Credit Unions in Indonesia.